The Diversity of Butterflies (Lepidoptera): A case Study of Changes in Butterfly Habitat due to Swamp Land Conversion (SLC) in Palembang Indonesia - Riyanto Riyanto; Rahmi Susanti; M. Aidil Fatha; Yunilda Rosa (Postgraduate, University of Mataram, 2025)
This study a specific case: whether alterations in butterfly habitats resulting from Swamp Land Conversion (SLC) impact the diversity, species count, and abundance of butterflies, which act as pollinating insects, within Palembang city. This study employs observational methods with a roaming technique, conducted five times at each research location. The research sites were determined using purposive sampling. The findings reveal a total of 230 individual butterflies from 19 species, distributed among five families: Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae, and Pieridae. The highest butterfly diversity index value is recorded at the Alang-Alang Lebar SLC location, whereas the lowest butterfly diversity index value is observed at the swamp land (SL) location. The most recent findings from this study is SLC lead to an increase in the diversity index, species count, and individual butterfly numbers of the Lepidoptera order, particularly in Alang-Alang Lebar SLC and Jakabaring SLC, as compared to SL location on Sungai Ijuk SL. The results suggest that SLC can contribute to the conservation of butterfly species belonging to the Nymphalidae, Papilionidae, Hesperiidae, and Lycaenidae families except the Pieridae family